A study of the yield and composition of the essential oils from Agathosma crenulata and A. betulina - Endenburg, H. G.(Henk Gerard) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1972.